The Influence Of Customer Personality On Product Preference - Yoga Bagus Pambudi; Pratami Wulan Tresna; Arianis Chan; Cecep Safa’atul Barkah (Business Journal : Jurnal Bisnis Dan Sosial, 2022)
A person's personality and characteristics are essential in determining anything, one of which is choosing to purchase products. Consumers prefer products that align with their personalities. It can be concluded that consumers will tend to choose products that satisfy their emotional feelings and are by the characteristics of these consumers. The method used by the author is quantitative. Quantitative methods are a systematic, planned, and structured type of research. From the discussion, it can be concluded that the customer personality variable significantly affects product selection. This is because consumers prefer to use products that align with their personalities.